E-Learning as Education Media Innovation inthe Industrial Revolution and Education 4.0 Era. - Dewi, R. Roro Vemmi Kesuma; Muslimat, Ade; Yuangga, Kharisma Danang; Sunarsi, Denok; Khoiri, Ahmad; Suryadi, Soleh; Solahudin, Makmur; Iswadi, Udi (The journal of contemporary issues in business and government, 2021)
In the era 4.0 industrial revolution the development of digital-based information and communication technology is increased. This needs to be used as best as possible to support the education and learning process, especially Islamic Religious Education. This study uses a qualitative research approach, this paper examines in depth the use of e- learning in learning at Senior High School in Tangerang, as an effort to respond to the presence of the 4.0 industrial revolution era with all the developments and advancements it brings. This paper concludes that the use of e-learning in Senior High School in Tangerang learning is intended to support learning activities so that learning becomes more innovative, interesting, fun, and not monotonous. In the application of e-learning, Senior High School in Tangerang implements a blended-learning system, which is a combination of face-to-face and distance learning. As for the implementation stage, Senior High School teachers in Tangerang have taken important stages related to the implementation of e-learning which includes need analysis, making instructional designs, using and developing e-learning stages, and evaluation.